Psychological well-being and demographic factors can mediate soundscape pleasantness and eventfulness: A large sample study. (October 2021) - Erfanian, Mercede; Mitchell, Andrew; Aletta, Francesco; Kang, Jian
Abstract: Soundscape studies aim to consider the holistic human perception of a sound environment, including both the physical phenomena and how these are mediated by internal factors. This study aims to assess the influence of psychological well-being and demographic factors including age, gender, occupation status, and education levels on the dimensions of the soundscape circumplex, i.e., Pleasantness and Eventfulness. Data was collected in eleven urban locations in London through a large-scale (N = 1134) soundscape survey according to the ISO 12913-2 technical specifications and incorporating the WHO-5 well-being index. Linear mixed-effects modelling applying backwards-step feature selection was used to model the interactions between internal factors including psychological well-being, age, gender, occupation status, education levels and the soundscape Pleasantness and Eventfulness, while accounting for the random effects of the survey location. The findings suggest that internal factors account for approximately 1.4% of the variance for Pleasantness and 3.9% for Eventfulness, while the influence of the locations accounted for approximately 34% and 14%, respectively. Psychological well-being is positively associated with perceived Pleasantness, while there is a negative association with Eventfulness only for males. Occupation status, in particular retirement as a proxy of age and gender, was identified as a significant factor for both dimensions. These findings offer empirical grounds for developing theories of the interaction between internal factors and soundscape formation whilst highlighting the importance of the location, namely: the context. Highlights: Understanding of the soundscape or sound perception is tied to certain key factors. LME modelling is conducted to examine the relationship between these key factors and the soundscape. Psychological well-being is positively associated with Pleasantness and negatively associated with Eventfulness. Occupation status, particularly retirement, is identified as a significant factor for both dimensions. . The personal factors account for 1.4% of the variance for Pleasantness and 3.9% for Eventfulness, and the locations accounted for 34% and 14%, respectively.